TANTANGAN MENGHADAPI PANDEMI COVID 19 DALAM PROSES PEMBELAJARAN BAHASA INDONESIA DI MAN MODEL PALANGKA RAYA - Mila Mila (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2020)
This research is a quantitative study that uses descriptive methods, namely making a systematic picture of some of the relationships to be studied. While the research instrument in his research used a questionnaire, which is a list of questions that have provided answers related to the factors causing learning difficulties. There is only one variable in this research or it is a mono variable or an independent variable. The mono variable is a factor that causes learning difficulties. The data mining tool used in this study was a questionnaire which was a data collection technique that was carried out by giving a set of written questions to the respondent to answer, so that the respondent only had to choose an alternative answer that was in accordance with the facts in the factors causing student learning difficulties.